2021
DOI: 10.1016/j.cmi.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Proton pump inhibitor use and risk for recurrent Clostridioides difficile infection: a systematic review and meta-analysis

Abstract: Objectives: Proton pump inhibitor (PPI) therapy is a potentially modifiable risk factor for recurrent Clostridioides difficile infection (CDI). Citing an absence of clinical trials, many guidelines do not provide recommendations for addressing PPI management. Our aim was to perform an updated systematic review and meta-analysis evaluating the association between PPI use and recurrent CDI addressing prior methodological limitations. Methods: Data sources were MEDLINE and EMBASE. Eligible studies were cohort and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
1
29
0
1
Order By: Relevance
“…With respect to PPIs, which are widely prescribed in Spain [34], they were classified as PIMs in 167 patients. PPIs may be related to adverse outcomes, such as fractures [35], hypomagnesaemia [36][37][38][39], recurrent C. difficile infection [40,41], dementia [42,43], communityacquired pneumonia [44], or severe COVID-19 infection [45][46][47]. Remarkably, in 160 (95.8%) patients, PPI prescription was assigned to implicit STOPP criterion A1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to PPIs, which are widely prescribed in Spain [34], they were classified as PIMs in 167 patients. PPIs may be related to adverse outcomes, such as fractures [35], hypomagnesaemia [36][37][38][39], recurrent C. difficile infection [40,41], dementia [42,43], communityacquired pneumonia [44], or severe COVID-19 infection [45][46][47]. Remarkably, in 160 (95.8%) patients, PPI prescription was assigned to implicit STOPP criterion A1.…”
Section: Discussionmentioning
confidence: 99%
“…The Updated Charlson Comorbidity Index [22] was calculated, adjusted by age and categorized by tertiles (2-6, 7-8 and 9-14). Barthel Index was categorized as independency (100 points), minimal dependency (60-95), moderate dependency (40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54)(55), severe dependency (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) and complete dependency (<20) [23]. Some chronic conditions were grouped according to clinical criteria, as in Baré et.al.…”
Section: Sampling and Analysismentioning
confidence: 99%
“…For instance, the data on the concurrent use of gastric acid suppressant par excellence such as pump proton inhibitors (PPIs) were too sparse to assess the potential interaction of OVP with PPIs on CDI occurrence. At any rate, considering the well-known role of PPIs as risk factor for CDI [ 6 ], a so-called stewardship of acid-suppressing medication is warranted through systematic de-prescribing [ 68 ] Another limitation concerns the safety profile of OVP, because the rate of VRE infections is not the best measure to assess its potential negative impact on microbiota. Instead, the rate of VRE colonization should be evaluated.…”
Section: Discussionmentioning
confidence: 99%
“…However, it was noted that the most recent (and largest) RCT did not demonstrate any effect of pantoprazole versus placebo on 90-day mortality and a composite outcome of clinically important events [494]. A recent meta-analysis published since the finalisation of the literature searches has suggested that there is a higher risk of recurrent Clostridioides difficile infections with proton pump inhibitors [495].…”
Section: Rationalementioning
confidence: 99%